HUBUNGAN INDEKS HARGA PROPERTI RESIDENSIAL DAN KREDIT PERBANKAN - Njo Anastasia; Fabian Hidayat (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2019)
Demand and supply in housing market depends on macroeconomic conditions such as Gross Domestic Product, interest rates, and housing prices. Changes to these variables are related to changes in housing market. This study aims to examine the relationship of housing prices, Gross Domestic Product, mortgage interest rate to Banking Credit. Knowing the relationship will be useful in making strategic decisions related to property investment and portfolio management. Housing price using Residential Price Index in primary market will be grouped into three parts based on land area of residential property consist of small house type, medium house type, and big house type. Data processing using Auto Regressive Distribution Lag (ARDL) bound test model to test the relationship between variables. The result of the research shows that there is a significant long run cointegration on the variable of housing price, Gross Domestic Product, and mortgage interest to banking credit. Furthermore, in testing each housing price group, the test results also show the relationship between these variables.